2018
DOI: 10.15294/jejak.v11i2.16061
|View full text |Cite
|
Sign up to set email alerts
|

Corruption, Poverty, and Economic Growth (Causality Studies among Asean Countries)

Abstract: Corruption has causal impacts on economic and social development indicators. The discussion on this issue is widely interesting among economists, especially in Southeast Asia Countries which have been considered that has as a corrupt governance system. The objective of this study is to analyze the causality of corruption, poverty, and economic growth among ASEAN countries between 2002 and 2015. Four countries have been choosen since they have the same characteristics in term of the indicators presented. Grange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Novriansyah (2018) also emphasized that poverty affects economic growth in Gorontalo Province. However, in Indonesia, Yunan & Andini (2018) found that poverty did not correlate with economic growth.…”
Section: Resultsmentioning
confidence: 95%
“…Novriansyah (2018) also emphasized that poverty affects economic growth in Gorontalo Province. However, in Indonesia, Yunan & Andini (2018) found that poverty did not correlate with economic growth.…”
Section: Resultsmentioning
confidence: 95%
“…Poverty is in line with human material condition that restricts basic needs optimization such as education, health, basic needs, and secondary needs. It is caused by insufficient income and limited living conditions, some developing countries poverty is generally caused by economic growth which tends to stagnate, development inequality, difficult employment opportunities, political policies tend to be unstable, and corruption and centralization system (Akhmad and Amir, 2018, Barnes, 2010, Guritno et al, 2018, Ighadalo, 2012, Obadan, 2002, Rustiadi, 2009, Sakinah and Pudjianto, 2018, Yunan and Andini, 2018. The impacts are the existence of slum area in the middle of the city but it is not worth to living in, health insurance is not optimal, limited access to resources, the low quality of education.…”
Section: Povertymentioning
confidence: 99%
“…Accordingly, this paper will focus more on the the quality of institution measurement provided by the World Bank's Worldwide Governance Indicators, which include government effectiveness, political stability and absence of violence/terrorism, regulatory quality, rule of law, voice and accountability. However, control of corruption will be excluded from the analysis since corruption's effect on economic performance has been widely discussed in various contexts of the kinds of literature (Shittu et al, 2018;Yunan & Andini, 2018;Sharma & Mishra, 2022;Spyromitros & Panagiotidis, 2022).…”
Section: Introductionmentioning
confidence: 99%